Pembuatan Nugget Ayam dengan Penambahan Puree Ubi Jalar Ungu dan Udang - Randika Lafia Dewi; Niken Purwidiani; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (Jurnal Bintang Pendidikan Indonesia, 2024)
Chicken nuggets with the addition of purple sweet potato puree and shrimp are innovative nuggets made from chicken meat, purple sweet potato, shrimp and spices. The experiment aimed to determine: 1) the best sensory test quality: 2) nutritional content, namely Protein, Fat, Carbohydrate, Antioxidant, Fiber; and 3) selling price 250 grams. research method used experiments to conduct 2 trials to determine best sensory test. Data collection techniques through sensory tests using instrument 30 panelists. Data analysis technique with quantitative descriptive analysis of percentages. results showed: 1) color sensory test results 22 (69%) light purple, 8 (25%) purple and 2 (6%) not purple, shape 16 (53%) love-shaped, 14 (47%) less perfect, aroma 21 (70%) smells combination of chicken and purple sweet potato, 7 (23%) combination of chicken and shrimp, 2 (7%) less flavorful shrimp and purple sweet potato, taste 20 (67%) moderately savory combination of chicken shrimp little sweetness purple sweet potato, 9 (30%) savory combination of chicken, shrimp, 2 (3%) sweet not savory purple sweet potato. Texture 18 (60%) soft chewy solid 12 (40%) solid; 2) laboratory test results content per 100 grams; Protein 12.83%, Carbohydrate 36.56%, Fat 6.05%, Antioxidant 92.88%, Fiber 3.22%; 3) Selling price 250 grams IDR 36.800.